2013
DOI: 10.4103/2249-4863.117405
|View full text |Cite
|
Sign up to set email alerts
|

HIV in females: A clinico-epidemiological study

Abstract: Background:Human Immunodeficiency Virusinfected women account for almost half the number of cases of HIV worldwide. Despite reduction in HIV prevalence among the population, the percentage of Indian women contracting the disease seems to have increased. The social implications are also different in females.Materials and Methods:This prospective observational study was conducted from September 2009 to July 2011 at tertiary care hospitals attached to the Kasturba Medical College Mangalore, on a group of 200 HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…The effects of such cultural constructions of women and sexuality have also been seen in the way women who engage in sex work have been regarded as a source of HIV infection by policy makers, especially in the initial days of the epidemic (Patton 1994 ). While it has been shown that most women in India have contracted HIV from their spouse, this has in no way diminished judgments regarding their sexual morality, with high levels of discrimination being reported, including by family members (Malave et al 2014 ; Padyana et al 2013 ).…”
Section: Sexuality and The Stereotyping Of Hiv Infection Among Womenmentioning
confidence: 99%
“…The effects of such cultural constructions of women and sexuality have also been seen in the way women who engage in sex work have been regarded as a source of HIV infection by policy makers, especially in the initial days of the epidemic (Patton 1994 ). While it has been shown that most women in India have contracted HIV from their spouse, this has in no way diminished judgments regarding their sexual morality, with high levels of discrimination being reported, including by family members (Malave et al 2014 ; Padyana et al 2013 ).…”
Section: Sexuality and The Stereotyping Of Hiv Infection Among Womenmentioning
confidence: 99%
“…In a study that comprises HIV-infected males and females with similar demographics and clinical characteristics, more females acknowledged asking clinicians about the symptoms of aging-related comorbidities and were provided such information without request. The study also revealed that 80% of females desired symptom-related information compared with 22% of males [36,38]. To date, little attention is given to interventions targeting HIV aging phenotypes and sex-based differences, with HIV-infected populations generally being ignored in intervention research [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Payana et al found in their study that, among male patients who did not know the HIV status of spouse the majority had not revealed their HIV status to the wife or had never asked the wife to get tested for HIV. 10…”
Section: Housewivesmentioning
confidence: 99%